Comprehensive Quantitative Proteome Analysis of Aedes aegypti Identifies Proteins and Pathways Involved in Wolbachia pipientis and Zika Virus Interference Phenomenon - Martins, Michele; Ramos, Luis Felipe Costa; Murillo, Jimmy Rodriguez; Torres, André; de Carvalho, Stephanie Serafim; Domont, Gilberto Barbosa; de Oliveira, Danielle Maria Perpétua; Mesquita, Rafael Dias; Nogueira, Fábio César Sousa; Maciel-de-Freitas, Rafael; Junqueira, Magno (Frontiers in Physiology, 2021)
Zika virus is a global public health emergency due to its association with microcephaly, Guillain-Barré syndrome, neuropathy, and myelitis in children and adults. A total of 87 countries have had evidence of autochthonous mosquito-borne transmission of Zika virus, distributed across four continents, and no antivirus therapy or vaccines are available. Therefore, several strategies have been developed to target the main mosquito vector, Aedes aegypti, to reduce the burden of different arboviruses. Among such strategies, the use of the maternally-inherited endosymbiont Wolbachia pipientis has been applied successfully to reduce virus susceptibility and decrease transmission. However, the mechanisms by which Wolbachia orchestrate resistance to ZIKV infection remain to be elucidated. In this study, we apply isobaric labeling quantitative mass spectrometry-based proteomics to quantify proteins and identify pathways altered during ZIKV infection; Wolbachia infection; co-infection with Wolbachia/ZIKV in the Ae. aegypti heads and salivary glands. We show that Wolbachia regulates proteins involved in ROS production, regulates humoral immune response, and antioxidant production. The reduction of ZIKV polyprotein in the presence of Wolbachia in mosquitoes was determined by mass spectrometry and corroborates the idea that Wolbachia helps to block ZIKV infections in Ae. aegypti. The present study offers a rich resource of data that may help to elucidate mechanisms by which Wolbachia orchestrate resistance to ZIKV infection in Ae. aegypti, and represents a step further on the development of new targeted methods to detect and quantify ZIKV and Wolbachia directly in complex tissues.